2017
DOI: 10.1112/plms.12026
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic dimension and small-cancellation for hierarchically hyperbolic spaces and groups

Abstract: We prove that all hierarchically hyperbolic groups have finite asymptotic dimension. One application of this result is to obtain the sharpest known bound on the asymptotic dimension of the mapping class group of a finite type surface: improving the bound from exponential to at most quadratic in the complexity of the surface. We also apply the main result to various other hierarchically hyperbolic groups and spaces. We also prove a small-cancellation result namely: if G is a hierarchically hyperbolic group, H G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 35 publications
0
85
0
Order By: Relevance
“…While this property is stronger (see [BHS15b,Section 7]), and somewhat more involved than coarse medians it is also substantially more powerful: it implies even finite asymptotic dimension [BHS15a]. Having finite asymptotic dimension is a strictly stronger property than Property A.…”
Section: Introductionmentioning
confidence: 99%
“…While this property is stronger (see [BHS15b,Section 7]), and somewhat more involved than coarse medians it is also substantially more powerful: it implies even finite asymptotic dimension [BHS15a]. Having finite asymptotic dimension is a strictly stronger property than Property A.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchically hyperbolic spaces are examples of coarse median spaces, see [2], hence our theorem is broader in scope, though with a weaker conclusion, than the finite asymptotic dimension result proven in [1]. We expect the following general result.…”
Section: Introductionmentioning
confidence: 78%
“…Among those are, for instance, finitely generated abelian groups, free groups of finite rank, Gromov hyperbolic groups [14,24], mapping class groups [5], CAT(0) cube complexes of finite dimension [29], see [3] for an excellent survey of these and other results. Recently Behrstock, Hagen and Sisto introduced the powerful new notion of hierarchically hyperbolic spaces and showed that these have finite asymptotic dimension [1], recovering a number of the above results, including notably mapping class groups and a number of CAT(0) cube complexes.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations